2012
DOI: 10.1007/s10120-012-0189-7
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori cagL amino acid polymorphisms and its association with gastroduodenal diseases

Abstract: CagL is a pilus protein of Helicobacter pylori that interacts with host cellular a5b1 integrins through its arginine-glycine-aspartate (RGD) motif, guiding proper positioning of the T4SS and translocation of CagA. Deletion or sequence variations of cagL significantly diminished the ability of H. pylori to induce secretion of IL-8 by the host cell. Therefore, this study was undertaken to investigate the association of cagL and its amino acid sequence polymorphisms with gastric cancer (GC), peptic ulcer disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 11 publications
5
33
1
Order By: Relevance
“…This finding is contrary to the study performed by Ogawa et al from Japan where A41 was only detected among CagL variants in GC isolates (2/10, 20%), although in a not significant relationship vs non‐GC isolates. In addition, the majority of our strains had Asparagine (N) at position 122, which is in line with the data obtained by Shukla et al from India where all of the strains were found to have N122 variant. In contrast, K122 was predominantly observed among Japanese and Taiwanese isolates .…”
Section: Discussionsupporting
confidence: 93%
“…This finding is contrary to the study performed by Ogawa et al from Japan where A41 was only detected among CagL variants in GC isolates (2/10, 20%), although in a not significant relationship vs non‐GC isolates. In addition, the majority of our strains had Asparagine (N) at position 122, which is in line with the data obtained by Shukla et al from India where all of the strains were found to have N122 variant. In contrast, K122 was predominantly observed among Japanese and Taiwanese isolates .…”
Section: Discussionsupporting
confidence: 93%
“…pylori -mediated proinflammatory responses. The amino acid polymorphism combinations examined in this study were: D58K59 and Y58E59 which have both been linked with increased gastric cancer risk [ 7 , 8 ]; and N58E59, N58K59 and D58E59 which have not shown a specific link to H . pylori disease progression [ 7 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Rizzato et al [ 9 ], the cagL gene shows 74 nucleotide polymorphisms, including 31 non-synonymous polymorphisms. To date, only a subset of these 31 amino acid polymorphisms have been examined for cancer association: Yeh et al examined residues 58, 59, 122, 201, 210, 216, 221 and 234 [ 7 ]; Shukla et al examined residues 35, 58, 59, 60, 62 and 122 [ 8 ]; and Rizzato et al examined residues 35, 55, 58, 60 and 176 [ 9 ]. Of these, only polymorphisms at amino acid residues 55 [ 9 ], 58 [ 7 9 ] and 59 [ 7 , 8 ] have been shown to correlate with host gastric cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also found that two novel strain-variable CagL loop motifs, TSPSA5343536 in loop 1, and TASLI (aa 170 to 175 in loop 4), are involved in determining the strength of integrin interaction (TSPSA and TASLI), or modulate CagL cell binding (TASLI). The first of these latter CagL segments has been previously highlighted: several research groups have determined an association between amino acid polymorphisms in this segment adjacent to TSPSA (in particular in amino acids 58 and 59) and the cancer risk of infected patients343643. There is conflicting evidence on the role of these amino acids, and the pathological association of polymorphisms has not been causally confirmed yet.…”
Section: Discussionmentioning
confidence: 99%